ANALISIS KEBUTUHAN TERMINAL AGROPOLITAN DI KABUPATEN GOWA - Khairul Sani Usman (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2015)
Gowa is one area that has a high potential in the agricultural sector . As one support agricultural development of the area needed a tool that can serve as a place to accommodate and distribution of agricultural goods, especially in rural areas can then add value to agricultural products so as to increase local revenues in Gowa. But in fact in Gowa is not available a facility that can accommodate and distribution of agricultural goods . Marketing activities and unloading of agricultural products are generally often take place in locations traditional markets and partly carried out at several locations that are not on the allotment, as in Jalan Poros Pallangga - Limbung the course of an arterial road function. Who every day experience the congestion caused by these activities. Based on the above issues will be carried out through research that this study is